Portais de governo eletrônico em Municípios do Estado da Paraíba: análise sob a óptica da segurança da informação - Sena, Alnio Suamy de (2017)
Electronic government can be characterized as the use of Information and Communication Technologies by public administration as support for internal government processes and the delivery of government products and services to citizens and industry in a fast and efficient way. It is essential that e-government prevents unauthorized access to ensure that Integrity, Availability and Confidentiality, basic principles of information security, are protected from electronic threats on the Internet. These threats place information assets at constant risk by taking advantage of the various vulnerabilities in the virtual environment where e-government is inserted. Thus, this research aimed to analyze the possible vulnerabilities in egovernment portals of the municipalities of Paraíba State. The 50 municipalities that represent the largest share of the Gross Domestic Product (GDP) of the state of Paraíba were considered as the research population. From these, it was possible to analyze the portals of 40. This research was characterized as a descriptive research, with a Quantitative approach. In order to collect data, we used Nestparker software, a vulnerability scanner whose function is to track and identify vulnerabilities in Web applications. As a result, 822 vulnerabilities were found, of which 15% are Critical and 15% High Criticality. In addition, 10% of the vulnerabilities were classified as Medium Criticality, which, in addition to other vulnerabilities with higher impacts, represents a scenario with more than 40% vulnerabilities found in the portals of the municipalities analyzed. Such vulnerabilities have the potential to allow malicious elements to negatively impact the continuity of the service. In addition to identifying the vulnerabilities of electronic security in e-government portals in the State of Paraíba, this research indicated how to correct the identified problems, which allows public managers to take actions that aim to minimize security breaches and the adoption of security strategies as well as the implementation of an information security policy.